Systems and Computational Biology Molecular and Cellular Experimental Systems - Yang, Ning-Sun (IntechOpen, 2011)
Whereas some "microarray" or "bioinformatics" scientists among us may have been criticized as doing "cataloging research", the majority of us believe that we are sincerely exploring new scientific and technological systems to benefit human health, human food and animal feed production, and environmental protections. Indeed, we are humbled by the complexity, extent and beauty of cross-talks in various biological systems; on the other hand, we are becoming more educated and are able to start addressing honestly and skillfully the various important issues concerning translational medicine, global agriculture, and the environment. The two volumes of this book presents a series of high-quality research or review articles in a timely fashion to this emerging research field of our scientific community.